Shared Decision Making for Surgical Care in the Era of COVID-19. (February 2021) - Forner, David; Noel, Christopher W.; Densmore, Ryan; Goldstein, David P.; Corsten, Martin; Pieterse, Arwen H.; Shuman, Andrew G.; Hong, Paul; Rac, Valeria E.
The global pandemic caused by severe acute respiratory syndrome coronavirus 2 has upended surgical practice. In an effort to preserve resources, mitigate risk, and maintain health system capacity, nonurgent surgeries have been deferred in many jurisdictions, with urgent procedures facing increasing wait times and unpredictability given potential future surges. Shared decision making, a process that integrates patient values and preferences with the scientific expertise of clinicians, may be of particular benefit during these unprecedented times. Aligning patient choices with their values, reducing unnecessary health care use, and promoting consistency between providers are now more critical than ever before. We review important aspects of shared decision making and provide guidance for its perioperative application during the coronavirus disease 2019 pandemic.